Effectiveness of Power Exercises Compared to Traditional Strength Exercises on Motor Skills, Muscle Performance and Functional Muscle Strength of Children with Attention Deficit Hyperactivity Disorder: A Single-Blind Randomized Controlled Trial. - Tascioglu, Elif Nur; Karademir, Selcen; Kara, Koray; Tonak, Hasan Atacan; Kara, Ozgun Kaya (Developmental Neurorehabilitation)
The aim of this study was to compare the impact of 8-weeks of power exercises compared to traditional strength exercises on motor abilities, muscle performance, and functional strength in children with ADHD. A total of 34 children with ADHD were randomized into two groups to receive functional power training (n = 17, M age: 121.2 ± 16.6 months) and traditional strength training (n = 17, M age: 116.1 ± 13.4 months). After the 8-week intervention, two-way ANOVA results with 95% confidence intervals showed no differences between the groups in motor skills, muscle power, or functional muscle strength. However, the functional power training group had larger effect sizes and greater increases in total motor composite score (10% vs 7%), body coordination (13.8% vs 4.9%) and bilateral coordination (38.8% vs 27.9%) than the traditional strength training group. The power training group also exhibited catch-up growth with typically developing peers. These findings suggest that power exercises may be more effective than strength exercises for rapid force generation in daily life, particularly for children with ADHD.